Monitoring the Use of Synthetic Pesticides for Pest and Disease Control of Rice Plants in Tidal Marshlands - Wagi, Wagiyanti; Hamidson, Hamidson; Suwandi, Suwandi; Umayah, Umayah (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
The majority of people in tidal marshland areas are farmers. Many of the crops grown by the community are food crops such as rice. Rice is one of the food crop commodities that has high economic value. In cultivating rice plants to improve the quality of production, farmers on tidal land currently use chemical pesticides as the most effective alternative source in controlling pests and diseases. This study aims to determine the various types of pests and diseases in rice plants, and the types of synthetic pesticides used by farmers in increasing awareness of the environment from good and proper agricultural practices. The research was conducted in 2023 during the rice season. The method of implementation was carried out by surveying 40 rice farmers in Air Salek District, Banyuasin Regency, namely interviewing according to the questionnaire. The results of the monitoring and interviews showed that the pests and diseases that attacked rice plants were False White Pest (Cnaphalocrosis medinalis), Rice Stem Borer, Brown Stem Leafhopper (Nilaparvata lugens), Armyworm (Spodoptera litura), Leaf Blast, and Neck Blast. There are two types of synthetic pesticides used to control pests and diseases, namely insecticides made from the active ingredient Klorpiripos with a percentage of 55% and 85% fungicides made from the active ingredient Trifloxystrobin 25%, Tebukunazol are in demand by farmers. In the application of synthetic pesticides farmers do not meet the standards due to the low education of farmers.